TINGKAT PENDAPATAN, KONSUMSI, DAN TABUNGAN KELUARGA PENGHASIL DAN PEDAGANG KECAMBAH KACANG HIJAU DI KECAMATAN BELITANG II OKU TIMUR - AISAH (Jurnal Bakti Agribisnis, 2019)
Mung bean sprouts are one of the sprouts / bean sprouts that are mostly used as food or consumption material in general, this is because the sprouts or bean sprouts from green beans contain a lot of gizi which is needed to facilitate defecation and to reduce obesity and increase fertility. Processing of green beans is expected to increase income which converts primary products into new products with higher economic value after going through the processing process, so it will be able to provide economic value because costs are incurred so that new higher prices are formed and the profits are greater than without going through the process processing. With this economic value, it causes an increase in the household income of farmers, which raises the potential for savings. The purpose of this study was to determine the level of income and business feasibility of mung bean sprouts in the East OKU Belitang II District, to determine the level of consumption and the level of savings of the green bean sprouts producer and trader in the East OKU Belitang II District. The results of the study concluded that the level of income obtained by the sprouts entrepreneur was Rp. 118,575 / process with the feasibility level of the sprouts business based on the ROI calculation of 56.03%, BEP for Rp. 6,827 / Kg and BEP for Production of 0.87 kg, Payback Period 3.57 and R / C of 1.56. The level of consumption of sprouts producers and traders is Rp 912,055 / month. The level of savings for sprouts producers and traders is Rp 866,567 / month.